A sensitive lanthanide label array method for rapid fingerprint analysis of plant polyphenols based on time-resolved luminescence. Issue 39 (26th September 2019) - Saha, Sanjib; Imran, Iqbal Bin
Abstract : For the first time, a novel lanthanide label array method was developed for rapid fingerprint analysis of plant polyphenols in a high throughput format. Abstract : Polyphenols are the most commonly available secondary metabolites with diverse bioactivities that vary with their chemical composition. Herein, fingerprint analysis of plant polyphenol composition is very crucial to reveal the overall bioactivities. In our current investigation, a generic and simplified method based on the time-resolved luminometric lanthanide label array technology has been developed for the rapid fingerprint analysis of plant polyphenols. This method works on the detection of the luminescence signal profiles specific to polyphenol compositions resulting from the nonspecific interaction of long-term unstable lanthanide chelates with polyphenols of plant samples. It is a simpler and cost-effective method in comparison to the many existing methods of polyphenol fingerprint analysis. This method allowed us to distinguish plant polyphenols based on their quenching effects on the luminescence in a time-dependent manner. Different samples provided different signal profiles based on their inherent polyphenol compositions. Principal component analysis (PCA) clearly clustered and distinguished oligomeric hydrolyzable tannin (HT) containing samples from the monomeric HT containing ones. UHPLC-DAD-ESI-MS identification and quantification of plant polyphenols was used as a reference for the validation of the method. Quantification results significantly correlated with the clustering of plant samples based on their polyphenol composition.